Perception of Hadiths on Bullying in Preventive Efforts Against Bullying in Inclusive Schools: A Study at SMA Daarul Abroor Lebak Wangi - Azhari, Ainul; Rahmawati, Aslihatul; Halimah, Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
Hadith or As-Sunnah is one of the sources of Islamic teachings that holds a highly significant position among prominent scholars of the past, both structurally and functionally. Structurally, it ranks second after the Qur'an, but functionally, it serves as a bayan (explanation) for the general or absolute verses of the Qur'an. This research seeks to examine the issue of bullying through the lens of the Prophet Muhammad’s hadiths, while also exploring how these teachings can be integrated into preventive strategies, especially within the context of inclusive educational settings. This study adopts a qualitative approach by applying a descriptive-analytical method within the structure of a case study. As a case study, this research is conducted through field research. For data analysis, the study also adopts a phenomenological approach to deeply examine individuals’ lived experiences related to bullying, a phenomenon frequently occurring in schools. The findings are then integrated with the Prophet’s hadiths and applied within the context of inclusive schools. The data were gathered using methods such as observation, interviews, and documentation. The analysis applies thematic methods and the science of ma’anil hadith (meanings of hadith). The results of this study have significant implications for educational practices in inclusive schools. First, understanding the Prophet’s hadiths on compassion, the prohibition of harming others, and the importance of brotherhood can serve as a foundation for cultivating an anti-bullying school culture. Second, a hadith-based religious approach can strengthen character education programs that are not only normative but also grounded in authoritative and contextual Islamic teachings. Third, this research provides a practical basis for schools—especially inclusive ones—to formulate preventive policies rooted in Islamic values, such as through curriculum development, school regulations, and student guidance activities. Fourth, from a pedagogical perspective, teachers should receive specialized training to integrate hadith values into learning processes and student mentoring approaches. Lastly, parental involvement in conveying and instilling hadith values at home plays a crucial role in building collective awareness of the dangers of bullying. Therefore, this study contributes not only theoretically to the field of hadith and Islamic education but also offers practical benefits in developing a more humane, religious, and socially safe inclusive educational ecosystem.